Protective Potential of Kersen Leaf Ethanol Extract (Muntingia calabura L.) Against Hepatic Histopathology in Diabetes Mellitus Model Rats - Nurlena Andalia; M. Ridhwan; Elvitriana; Armi; Jailani (Jurnal Penelitian Pendidikan IPA, 2025)
Kersen leaves (Muntingia calabura L.) are known as herbal plants used to lower blood glucose levels. This study evaluated the protective effect of ethanol extract of kersen leaves on the histopathology of the liver of white rats (Rattus norvegicus) model of diabetes mellitus. The experimental study with a Complete Randomized Design (RAL) involved five treatment groups and three replicates, using 55 streptozotocin (STZ)-induced mice. The results showed that the administration of 15% (K5) of kersen leaf ethanol extract improved the structure of hepatocytes, resembling normal tissue, compared to the positive control group (K2) who experienced severe necrosis and degeneration. In conclusion, 15% kersen leaf ethanol extract is effective in improving liver damage due to diabetes and potentially lowering blood glucose levels.